Experimental acidification increases susceptibility of Mercenaria mercenaria to infection by Vibrio species. (February 2020) - Schwaner, Caroline; Barbosa, Michelle; Connors, Peter; Park, Tae-Jin; de Silva, Darren; Griffith, Andrew; Gobler, Christopher J.; Pales Espinosa, Emmanuelle; Allam, Bassem
Abstract: Ocean acidification alters seawater carbonate chemistry, which can have detrimental impacts for calcifying organisms such as bivalves. This study investigated the physiological cost of resilience to acidification in Mercenaria mercenaria, with a focus on overall immune performance following exposure to Vibrio spp. Larval and juvenile clams reared in seawater with high p CO2 ( ~ 1200 ppm) displayed an enhanced susceptibility to bacterial pathogens. Higher susceptibility to infection in clams grown under acidified conditions was derived from a lower immunity to infection more so than an increase in growth of bacteria under high p CO2 . A reciprocal transplant of juvenile clams demonstrated the highest mortality amongst animals transplanted from low p CO2 /high pH to high p CO2 /low pH conditions and then exposed to bacterial pathogens. Collectively, these results suggest that increased p CO2 will result in immunocompromised larvae and juveniles, which could have complex and pernicious effects on hard clam populations. Highlights: Clams in high p CO2 /low pH were more susceptible to infection by pathogenic Vibrios. Growth and abundance of Vibrio spp. were greater under high p CO2 /low pH. Clams reared under high p CO2 /low pH seemed to have a broad tolerance range for pH. Long-term effect of acidification and susceptibility to vibriosis is understudied.